Evaluation of reproductive potential after intracytoplasmic sperm injection of varied human semen tested by antiacrosomal antibodies - Teplá, Olga; Pěknicová, Jana; Kočí, Karel; Míka, Josef; Mrázek, Milan; Elzeinová, Fatima (Fertility and sterility, 2006)
OBJECTIVE: To determine whether varied human spermatozoa, as detected with monoclonal antibodies against acrosomal proteins, have an influence on fertilization, transfer, pregnancy, and implantation rates when intracytoplasmic sperm injection is used. DESIGN: A retrospective study. SETTING: A private IVF center and academic research laboratory. PATIENT(S): One thousand two hundred forty men participating in the intracytoplasmic sperm injection program. INTERVENTION(S): Sperm were divided into seven groups: oligozoospermia, oligoasthenozoospermia, and oligoasthenoteratozoospermia and fresh and frozen-thawed epididymal and fresh and frozen-thawed testicular sperm. Fertilization, transfer, pregnancy, and implantation rates were recorded in each category. Sperm were tested with antibodies for detection of the of the sperm acrosome. MAIN OUTCOME MEASURE(S): Fertilization, transfer, pregnancy and implantation rates, and percentage of acrosome-reacted cells. RESULT(S): The fertilization rate and statistical evaluation showed differences between morphologically normal and pathological sperm and other groups. The freezing-thawing procedure had no influence on the fertilization of testicular sperm, but epididymal frozen-thawed sperm had a higher fertilization rate. Immunofluorescence proved decreasing sperm quality in all groups compared with the control group. This difference is not manifested in other parameters (transfer, pregnancy, implantation rates). CONCLUSION(S): The spermatozoa with varied semen characteristics and good quality, also detected with specific antibodies, gave the best fertilization rates. The paternal effect is not proved in other parameters.
Keywords: těhotenství; hodnocení výsledků zdravotní péče; Cells, Cultured; Immunoassay; retrospektivní studie; Humans; akrozom; Infertility, Male; úhrn těhotenství na počet žen v reprodukčním věku; Financing, Organized; financování organizované; Acrosome; imunoanalýza; mužské pohlaví; výsledek terapie; Antigen-Antibody Complex; Pregnancy Rate; imunokomplex; kultivované buňky; Treatment Outcome; ženské pohlaví; mužská infertilita; sperma; Sperm Injections, Intracytoplasmic; intracytoplazmatické injekce spermie; lidé; Pregnancy; Semen; Male; Retrospective Studies; Outcome Assessment, Health Care; Female